Standard operating procedure for characterization of instrumental texture of steamed potato by penetration, TPA and extrusion - Nakitto, M.; Moyo, M.; Mendes, T.; Balikoowa, B.; Ssali, R.T.; Ayetigbo, O.; Mestres, C. (2024)
Consumers of potato in Uganda prefer potato tubers that are soft when cooked. Softness is commonly used as an antonym for firmness. Therefore, consumers like potatoes that require little effort to bite through. This SOP describes laboratory-based methods for measuring instrumental texture in steamed potato. The methods described include details about sample preparation, conditions of instrumental texture analysis and description of textural parameters measured. To cook the samples, cubed pieces measuring 2.5cm on each side were excised from potato tubers and steamed between pieces of banana leaves over boiling water for 15 minutes. A similar procedure is used when preparing potato samples for descriptive sensory analysis where whole tubers are peeled and steamed between layers of banana leaves over boiling water for 40 minutes. The proposed texture analysis procedure is conducted on 2.5 cm cubes of potato using a 60° conical probe to a maximum distance of 10 mm for penetration, 75mm cylindrical plate for two-cycles texture profile analysis (TPA), and 5-blade grid Ottawa cell for extrusion. The methods were validated by comparing with descriptive sensory analysis of steamed potato on the same samples, and significant correlations were found. While all the methods were discriminant, the penetration method seemed to be preferred in lieu of extrusion and texture profile analysis.